Dietary Inclusion of Palm Oil in Bangladeshi Dietensures Better Nutrition with Minimal Cost: An Overview - Goon, Shatabdi (Journal of Food Technology Research, 2014)
The paper outlines the situation, consumption and importation of fats and oils in Bangladesh considering its latest trend of marketing with palm oil covered by health and economic issue. Recommended dietary intake of fats and oils are missing from Bangladeshi diet having poor knowledge regarding its importance and low purchasing ability. In this regards, Palm oil being the cheapest commodity vegetable oil and also the cheapest oil to produce and refine, can be an important component of the increasing intake of oils and fats in the developing world like Bangladesh. Compared with other imported edible oils, Palm oil having better nutrition value and low cholesterol as well as price and import cost has gained much attention by Bangladeshi government in recent years. The active presence of different suppliers of palm oil, direct interactions between suppliers and local importers and refiners can uplift the present situation of oils and fats consumption aiming popularity for palm oil in Bangladesh.